Prediction of ferromagnetic characteristics of gold doped SiC nanotubes for application in spintronic devices - Jafarova, V.N; Eminova, V.I; Musaev, M.A; Scurtu, I. C (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Single walled (6,0) gold doped SiC nanotube systems were studied by first principles modeling. We observed the electronic structures of SiC nanomaterials are significantly modified by the introduction of gold, and these systems exhibit magnetic properties. While the configurations of single walled (6,0) gold doped SiC nanotubes, the energy gap width of the spin-up states decreases, and these systems exhibit a semi-metallic character. Partial density of states analysis shows that the electron orbitals arise from contributions from the C p orbitals and the 4d transition metal d orbitals. First principles results of total energy predicted the stability of the antiferromagnetic phase.